Audit Forensik Untuk Pencegahan Korupsi Dengan Menggunakan Whistleblowing Untuk Deteksi Suap - Ailani Almira Hartono Putri; Sri Trisnaningsih (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The purpose of this study is to determine the effectiveness of forensic audits to detect bribery with whistleblowing support and the role of the KPK in preventing corruption in the Covid-19 disaster budget funds. This study uses a qualitative descriptive method by observing and analyzing all information related to the research topic both through (literature review, literature research, library research, and combined with previous research in order to explain the phenomena that will occur. From the results of this study, it can be concluded that forensic audit very effective for detecting bribes using the support of the whistleblowing system.